Luvsandanzanzhaltsan (1639–1704) and his Role in the History of Buddhism in Mongolia - Tsymzhit P. Vanchikova (Монголоведение)
Introduction. The article examines the biography of the first Lamyn-gegen Luvsandanzanzhaltsan and his activities in spreading Buddhism in Khalkha-Mongolia in the 17th century. As it is known, biographies of Mongolian lamas are valuable sources not only on the history of Buddhism, but also on general history of Mongolia, which contain information about certain events that have not been preserved in other historical chronicles or documents. The Mongolian lamas Ündür-gegen (1635–1723), Luvsandanzanzhaltsan (1639–1704) and Zaya-pandita Luvsanprinlai (1642–1715) played an important role in the successful spread of Buddhism in Khalkha Mongolia. If the life and activities of Ündür-gegen and Zaya pandita, their role in the history are well studied, the same cannot be said about Luvsandanzanzhaltsan, known as Lamyn-gegen. The purpose of this article is to fill in the gaps about the initial stage of the spread of Buddhism among the Khalkha-Mongolian principalities and about Luvsandanzanzhaltsan, one of the key figures in this process. Materials and methods. Mongolian-language translations of his biography written in Tibetan by Luvsanprinlai, published archival documents on the history of Mongolian monasteries and historical chronicles, publications by D. Dashbadrakh, R. Byamba, D. Ganzorig, S. Soninbayar, S.-I. Yundenbat, containing information on the subject, have been the main sources for the article. Their analyses became the basis for estimating his contribution to the spread of Buddhism and his role in the history of Mongolia in the second half of the 17th century. Within the framework of the study, a set of general scientific and special historical methods was used, which allowed us to consider the role of Lamyn-gegen in connection with the history of Mongolian society of the period under consideration. Results. The biography of Lamyn-gegen, the stages of his studying and becoming a major religious figure are considered. His role in the preparation of lamas and the construction of monasteries is described and brief information about his subsequent reincarnations is given. Attention is paid to the economic basis of the existence of his monasteries and the formation of the institute of shabinars. Conclusions. The results of the study allow us to conclude that Lamyn-gegen has made a great contribution into the spread of Buddhism in Mongolia, alongside with distributing Buddhist teaching and achievements of the centuries-old experience of medieval scientific knowledge of the East. He was the first Mongolian astrologer and emchi-lama, doctor, who has laid the foundation for the study of the heritage of Indo-Tibetan medicine and the creation of its Mongolian branch. He was also a translator of many treatises from Tibetan into Mongolian and a prominent scholar, whose works have been published in 4 volumes.